SENAM ASIK DAPAT MENURUNKAN NYERI MUSKULOSKELETAL PADA KELOMPOK WANITA TANI - Sumardiyono, Sumardiyono; Fajariani, Ratna; Chairunisa, Nabila Dian; Yasmine, Amalia; Avrilla, Syafina Nadya; Zakaria, Rais Athfal; Anugraeni, Devitasari; Mudrikah, Halimatul; Azzahra, Nirwana Putri; Kamil, Izzan; et al. (Media Penelitian dan Pengembangan Kesehatan, 2024)
Work-related musculoskeletal pain is a serious occupational health problem worldwide. Farmers are one of the groups of people who are most at risk of developing this condition. To help reduce musculoskeletal pain, farmers can participate in a exercise program called "Anti Sakit Ibu Kelompok wanita tani" (ASIK). The purpose of this study is to analyze the effect of ASIK-exercise on musculoskeletal pain in a group of women farmers in Karanganyar. The study used a pre-test and post-test design. The sampling technique used was purposive sampling, with a sample (respondents) of 19 women farmers who met the inclusion and exclusion criteria. The inclusion criteria were active members of the women farmers’ group, in good health, and living in the village of Bolon. The exclusion criteria were respondents who could not read or write, and who were unable to do exercises due to physical constraints. The independent variable was ASIK gymnastics, the dependent variable was musculoskeletal pain, and the control variable was age. The analysis of the difference in musculoskeletal pain scores before and after ASIK-exercises without controlling age used a paired samples t-test, and the analysis of the difference in musculoskeletal pain scores before and after ASIK-exercises with age as a covariate was performed using ANCOVA at α = 5%. The test results stated that with controlling age, ASIK-exercises can significantly reduce musculoskeletal pain (F = 7.540; p = 0.009) with a large effect size category (d = 1.68).